Ecological risks from zinc contamination to preys of the Irrawaddy dolphin (Orcaella brevirostris) in Banten Bay. (July 2018) - Khalifa, M A; Kamal, M M; Adiwilaga, E M; Sunuddin, A
Abstract: Banten Bay is an estuarine ecosystem which serves as important habitat for Irrawaddy dolphin (Orcaella brevirostris), also functions as a fishing ground for artisanal fishers, maritime port, shipyard, and surrounded by industrial zones. One major impact from land-based industrial development is the load of heavy metal pollution (Zinc –Zn), which cause a potential threat to Irrawaddy dolphin population as a predator in the ecosystem through bioaccumulation process from its prey. This research aimed to measure ecological risks in Irrawaddy dolphin due to Zn contamination in its potential prey, i.e., sardines (Sardinella fimbriata) and squids (Loligo sp.). Survey on dolphin population was conducted in Banten Bay from Jan 2013 to Feb 2014 with participatory mapping and visual observation, while Zn concentration in dolphin's preys was measured using Atomic Absorption Spectrophotometer (AAS) and analyzed by Risk Quotient (RQ) with base assumption that Maximum Allowable Concentration (MAC) of Zn is 6.7 mg/kg wet weight. Results showed that concentration of Zn in squids (7.67±1.02 mg/kg WW) was higher than that of sardines (3.46±0.29 mg/kg WW). Thus, squids have a moderate risk, while sardines have low risk to bioaccumulation of Zn in Irrawaddy dolphin.